La Formación del País de los Argentinos de Vázquez-Rial, Horacio Buenos Aires, 1999, Editorial Vergara, 410 págs. - Alles, Santiago Manuel (2001)
Fil: Alles, Santiago M. Pontificia Universidad Católica Argentina; Argentina